Cerebrospinal fluid antibodies to aquaporin-4 in neuromyelitis optica and related disorders: frequency, origin, and diagnostic relevance - Jarius, Sven; Franciotta, Diego; Paul, Friedemann; Ruprecht, Klemens; Bergamaschi, Roberto; Rommer, Paulus S.; Reuss, Reinhard; Probst, Christian; Kristoferitsch, Wolfgang; Wandinger, Klaus Peter; Wildemann, Brigitte (Journal of neuroinflammation, 2010)
In 70-80% of cases, neuromyelitis optica (NMO) is associated with highly specific serum auto-antibodies to aquaporin-4 (termed AQP4-Ab or NMO-IgG). Recent evidence strongly suggests that AQP4-Ab are directly involved in the immunopathogenesis of NMO.
Gesehen am 26.07.2023